Analysis Of Clean Water Use And Percentage Of Diarrhea Disease In Communities In Indra Jaya District, Aceh Jaya District, 2023 - Hidayattullah, Mhd.; Ulfa, Natasya (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
This research aims to analyze the relationship between clean water usage and the percentage of diarrhea incidence in the community of Indra Jaya, Aceh Jaya Sub-district, Surabaya. The study focuses on the primary water sources used by residents, environmental sanitation conditions, and household water treatment practices. The research employed data collection through questionnaires and observations, alongside statistical analysis to assess the relationship between water sources and the incidence of diarrhea. The results indicate that the majority of respondents use river and well water as their main water sources, with a 53.3% incidence of diarrhea. Statistical analysis reveals a significant correlation between poor water sources and a high percentage of diarrhea incidence. Environmental sanitation conditions, particularly the practice of personal hygiene (Mandi, Cuci, Kakus), also influence the risk of diarrhea, especially for those using river water. The importance of household water treatment, such as boiling, as an effective measure to prevent diarrhea, is highlighted in this research. Additionally, the study underscores the role of increasing community awareness regarding the cleanliness of water sources and environmental sanitation in reducing the risk of diarrhea. To decrease the incidence of diarrhea, preventive measures involving the government and healthcare professionals are recommended, including improving community access to safe water and conducting routine sanitation inspections to ensure the safety of water sources.